A systematic review of the evidence on spontaneous resolution of laryngomalacia and its symptoms. (April 2016) - Isaac, Andre; Zhang, Han; Soon, Sue Rene; Campbell, Sandra; El-Hakim, Hamdy
Abstract: Introduction and objectives: Laryngomalacia (LM) is the most common cause of congenital stridor. Tradition holds that the majority of patients resolve spontaneously by 12–18 months of age. The objective of this study was to systematically review the literature on the spontaneous resolution of LM and/or its presenting symptoms, in otherwise healthy infants. Methods: Data sources included Medline/PubMed, EMBASE, Scopus, CINAHL, Proquest, Cochrane database, Cochrane Methodology Register, Web of Science Conference Proceedings Citation Index, and ACP Journal Club. Study inclusion criteria included participants with an endoscopic diagnosis of LM, and symptoms of stridor, swallowing dysfunction, and/or snoring/sleep-disordered breathing, that documented subjective or objective resolution endpoints. Surgical series, case reports, and narrative reviews were excluded. Studies with insufficient follow-up (<3 months), and patients with comorbidities without subgroup analysis were excluded. Two independent reviewers extracted follow-up duration, rate of retention, time to resolution of LM, and method of documentation of resolution. Results: Of the 1146 articles identified, three met inclusion/exclusion criteria ( n  = 411 patients). All were retrospective and used stridor resolution as the only endpoint. Resolution rate was 89%, with time to resolution ranging from 4 to 42 months. Level of evidence was low, and studies suffered from lack of follow-up, and no objective endpoints. Meta-analysis was not possible. Conclusions: Endoscopic evidence of the natural history of laryngomalacia and its resolution is lacking. Low level of evidence supports that stridor and respiratory distress resolve, but the range of the time to resolution and rate of resolution is wide. Other clinical manifestations have not been studied. Prospective longitudinal trials are required to better understand the natural history.